2017
DOI: 10.1038/s41598-017-02750-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamics of endogenous fluctuations predict cognitive flexibility in the Go/NoGo task

Abstract: Fluctuations with power-law scaling and long-range temporal correlations (LRTCs) are characteristic to human psychophysical performance. Systems operating in a critical state exhibit such LRTCs, but phenomenologically similar fluctuations and LRTCs may also be caused by slow decay of the system’s memory without the system being critical. Theoretically, criticality endows the system with the greatest representational capacity and flexibility in state transitions. Without criticality, however, slowly decaying sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 46 publications
7
77
2
Order By: Relevance
“…However, these indicated moderate reliability at most (α = .61 for circle drawing and .56 for tapping). Simola et al (2017) ran their task twice on each participant, changing only a taskirrelevant feature of the stimulus (colour), and found no significant differences in either the autocorrelation, the PSD, or the DFA between time 1 and 2. However, nonsignificant results are difficult to interpret, and this analysis does not give an estimate of the extent of repeatability.…”
Section: Individual Differencesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these indicated moderate reliability at most (α = .61 for circle drawing and .56 for tapping). Simola et al (2017) ran their task twice on each participant, changing only a taskirrelevant feature of the stimulus (colour), and found no significant differences in either the autocorrelation, the PSD, or the DFA between time 1 and 2. However, nonsignificant results are difficult to interpret, and this analysis does not give an estimate of the extent of repeatability.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Two recent studies have aimed to link temporal structures to individual differences in performance. Firstly, Simola et al (2017) extracted the DFA slopes from the RT of a Go/No-Go task. They found that participants with steeper DFA slopes made less commission errors on the task (r-value = -.35), but found no correlation with mean RT or standard deviation of RT.…”
Section: Individual Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the reverberating regime covers a specific range ideal baseline [25] from which brain areas or neural circuits can 357 adapt to meet task demands [35,[46][47][48][49][50][51][52].…”
mentioning
confidence: 99%